Energy capability improvement of power DMOS transistors operating in pulsed conditions. (January 2015) - Costachescu, Dragos; Pfost, Martin
Highlights: A method of increasing the pulsed SOA of power DMOS transistors is proposed. Device peak temperature is lowered by the changing the power in different DMOS parts. The implementation requires only simple layout and driver circuit changes. Measurements show increases of the pulsed SOA between 9% and 39%. Abstract: Modern power DMOS transistors greatly benefit from the continuous advances of the technology, which yield devices with very low area-specific R DS, on figures of merit and therefore allow for significantly reduced active areas. However, in many applications, where the devices must dissipate high amounts of energy and thus are subjected to significant self-heating, the active area is not dictated by R DS, on requirements, but by the energy constraints. In this paper, a simple method of improving the energy capability and reliability of power DMOS transistors operating in pulsed conditions is proposed and experimentally verified. The method consists in redistributing the power density from the hotter to the cooler device regions, hence achieving a more homogeneous temperature distribution and a reduced peak temperature. To demonstrate the principle, a simple gate offset circuit is used to redistribute the current density to the cooler DMOS parts. No technology changes are needed for the implementation, only minor changes to the driver circuit are necessary, with a minimal impact on the additional required active area. Improvements in the energy capability from 9.2% up to 39% have been measured. Furthermore, measurements have shown that the method remains effective also if the operating conditions change significantly. The simplicity and the effectiveness of the implementation makes the proposed method suitable to be used in a wide range of applications.